Rheological study of genipin cross-linked chitosan hydrogels - Moura, M José; Figueiredo, M Margarida; Gil, M Helena (Biomacromolecules, 2007)
This paper reports the rheological behavior of chitosan solutions that have been cross-linked with different amounts of genipin, at body temperature and physiological pH. The effect of the cross-linker loading on the rheological properties of hydrogels has been evaluated. The oscillatory time sweep method was used to monitor the dynamic viscoelastic parameters during in situ (i.e., in the rheometer) gelation experiments, enabling the determination of the gelation time. The stress and frequency sweeps were employed to measure G' of the cured hydrogels. It was found that the solutions of chitosan cross-linked with genipin, under physiological conditions, could form relatively strong elastic gels when compared to those of pure chitosan. Moreover, the gelation time obtained from the crossover of G'' and G' was in excellent agreement with the value obtained from the Winter-Chambon criterion. A significant reduction on this parameter was achieved even at low genipin concentrations. This behavior suggests that these formulations are able to be produced in situ and thus constitute promising matrices for cells and bioactive molecule encapsulations.